Expression analysis of the heat shock protein genes and cellular reaction in dojo loach (Misgurnus anguillicaudatus) under the different pathogenic invasion. Issue 95 (December 2019) - Cheng, Jia; Li, Honghui; Huang, Zhenyu; Zhang, Fangliang; Bao, Lingsheng; Li, Yulong; Chen, Lin; Xue, Liangyi; Chu, Wuying; Zhang, Jianshe
Abstract: As molecular chaperones, heat shock proteins (HSPs) play essential roles in cells in response to stress conditions. Recent studies about immune functions of HSPs in fish have also been reported. In this study, based on the reported cDNA sequences of the four HSP genes, HSP70, HSC70, HSP90α and HSP90β, the temporal expression patterns of the four genes during embryonic development of dojo loach( Misgurnus anguillicaudatus ) was assayed with qRT-PCR. All of the four genes were ubiquitously expressed in all detected embryonic developmental stages. Among of them, HSP70, HSC70 and HSP90β were highly expressed in the organ formation stage, while HSP90α was the highest expressed in myotome formation stage. Further, the immune responses of the four HSP genes were assayed when loach were infected with three different pathogens, bacterium ( Flavobacterium cloumnare G4), parasite ( Ichthyophthirius multifiliis ) and fungus ( Saprolegnia ). All of the four genes were differentially expressed in four tissues such as skin, gills, spleen and kidney in response to the pathogenic invasion, but both HSP70 and HSP90α expressions were dramatically up-regulated. Further, the cellular responses of the loach skinand gill tissues were observed, in which the number of the skin goblet cells were significantly increased, and the gill lamellae became shorter and wider after infected. Thus, our work indicated that the HSPs may directly or indirectly involved in immune defense in fish, at least in the loach. Highlights: The expression patterns of HSP70, HSC70, HSP90α and HSP90β in different embryonic development stages of loach were analyzed. The HSP proteins exhibited deferentially expressed in response to the different pathogenic invasion of loach. Our work indicated that the HSPs may directly or indirectly involved in immune defense in fish, at least in the loach.